Synthesis, structure and characterisation of late transition metal complexes with 2-(tetrazol-1-yl)pyridine - Serebryanskaya, Tatiyana V.; Belavusava, Hanna A.; Grigoriev, Yuri V.; Voitekhovich, Sergei V.; Ivashkevich, Ludmila S.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2022)
Complexes [MII(2-pytz)Cl2] (M(II) = Pt, Pd; 2-pytz = 2-(tetrazol-1-yl)pyridine) were synthesised via direct interaction of the corresponding metal chlorides (K2PtCl4 or PdCl2) with 2-pytz under ambient conditions. RuCl3 does not react with 2-pytz under reflux in the protic media, while under reflux in N, N-dimethylformamide in the presence of LiCl, decomposition of the tetrazole cycle occurred leading to the formation of Ru(III)-coordinated N, N-dimethyl-N ′-(pyridin-2-yl)formimidamide derivative Li[RuIII(Py — N =C — NMe2)2Cl2]. The complex [Ru(2-pytz)(DMSO)3Cl2] ⋅ MeOH, where DMSO is dimethyl sulfoxide, was synthesised by reacting a specially prepared precursor cis-[Ru(DMSO)4Cl2] with 2-pytz in methanol under reflux conditions. The complex [Ru(2-pytz)(DMSO)2Cl2] was synthesised by reacting cis-[Ru(DMSO)4Cl2] with 2-pytz in ethanol under reflux conditions. The resulting complexes were characterised by elemental analyses, electrospray ionisation mass-spectrometry with detection of positive and negative ions, infrared spectroscopy, 1H and 13C nuclear magnetic resonance (NMR) spectroscopy, and simultaneous thermal analysis. The structures of complexes [Pd(2-pytz)Cl2] and [Ru(2-pytz)(DMSO)3Cl2] ⋅ MeOH were investigated by single-crystal X-ray analysis. In the former, 2-pytz shows a N,N-chelating coordination via the pyridine ring N and the tetrazole ring N2 atoms. In the latter, 2-pytz coordinates as a monodentate ligand via the tetrazole ring N4 atom. According to 1H NMR spectroscopy data, in complex [Ru(2-pytz)(DMSO)2Cl2], 2-pytz coordinates as a N, N-chelating ligand via the pyridine ring N and the tetrazole ring N2 atoms.